Comparison of Injection Sclerothetapy and Laser Photocoagulation for Bleeding Peptic Ulcers - Pulanić, Roland (Array, 1995)
The most widely used endoscopic procedures in the management of patients with bleeding peptic ulcer are at present sclerotherapy and thermal methods. In an attempt to assess the most effective method of achieving hemostasis, we compared injection sclerotherapy and laser photocoagulation in terms of the efficacy of initial hemostasis, rebleeding, need for surgery, mortality, and the appearance of the ulcer after the hemostatic procedure.In this prospective, randomized trial, 160 patients were treated with injection sclerotherapy (1% polidocanol), and 155 patients with laser photocoagulation (Nd:YAG laser) in cases of Forrest I, Forrest IIa, and Forrest IIb hemorrhage. The bleeding activity was classified according to the modified Forrest criteria. Polidocanol injection and Nd:YAG laser photocoagulation were not preceded by epinephrine administration. There were no significant overall differences between the groups in the outcome in terms of definitive hemostasis, rebleeding, urgent surgery, and death (p = 0.487). In the case of the subgroup with Forrest I lesions, laser photocoagulation was more efficacious than sclerotherapy (p = 0.0078), In the Forrest IIa and Forrest IIb subgroups, the two methods were equally effective (p = 0.202 and 0.513 respectively). In the sclerotherapy patients, definitive initial hemostasis in Forrest IIa was achieved in 100%, whereas in the laser group this rate was 92%, with 28% of patients initially developing hemorrhage after one or two laser pulses, Ulcer healing was slower following sclerotherapy than after photocoagulation. Injection sclerotherapy and laser photocoagulation are equally effective in achieving definitive hemostasis in bleeding peptic ulcers, Laser photocoagulation is more efficacious in patients with active bleeding, whereas injection sclerotherapy is more effective in patients with a nonbleeding visible vessel.